Pengembangan Website Perpustakaan Sekolah dengan Model Prototyping untuk Meningkatkan Efisiensi Layanan Mi Ma’arif Nu Karangasem - Megatamara Rosiana; Fersellia (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2026)
School libraries that rely on manual management often experience slow administrative processes, data recording errors, and inefficient services. This study aims to develop a web-based library information system using the Research and Development (R&D) method with a prototyping approach to improve library service quality at MI Ma'arif NU Karangasem. The development process consisted of requirements analysis, system design, implementation, testing, and evaluation. Functional testing was conducted using Black Box Testing, while usability was evaluated using the System Usability Scale (SUS) involving 10 respondents. The evaluation was complemented by User Acceptance Testing (UAT) and system performance testing. The results showed that all system functions operated successfully, achieving a 100% success rate in Black Box Testing. The system obtained a SUS score of 73, classified as Acceptable, Grade C, and Good, with a Cronbach's Alpha value of 0.93, indicating excellent instrument reliability. The UAT produced a 90% user acceptance rate. In addition, the system improved library service efficiency by reducing book search time by 90%, borrowing transaction time by 83.3%, and report generation time by 93.3%. These findings indicate that the proposed system is effective in improving the efficiency, usability, and quality of school library management.